Further structural and functional properties of mini‒lipoxygenase, an active fragment of soybean lipoxygenase-1. Issue 2 (2004) - Maccarrone Maccarrone, Mauro Mauro; Di Venere Di Venere, Almerinda Almerinda; van Zadelhoff van Zadelhoff, Guus Guus; Mei Mei, Giampiero Giampiero; Veldink Veldink, Gerrit Gerrit; Rosato Rosato, Nicola Nicola; Finazzi-Agrò Finazzi-Agrò, Alessandro Alessandro
Abstract : Lipoxygenases (Loxs) form a homologous family of non-heme, non-sulfur iron containing lipid-peroxidizing enzymes, which catalyze the dioxygenation of polyunsaturated fatty acids to the corresponding hydroperoxy derivatives. Soybean lipoxygenase-1 (Lox-1) is widely used as a prototype for studying the structural and functional properties of lipoxygenases. Tryptic digestion of soybean Lox-1 is known to produce a 60 kDa fragment, termed "mini-Lox", which shows enhanced catalytic efficiency and higher membrane binding ability than the native enzyme (M. Maccarrone, M.L. Salucci, G. van Zadelhoff, F. Malatesta, G. Veldink, J.F.G. Vliegenthart and A. Finazzi-Agrò, Biochemistry 40 (2001), 6819–6827). In this study, we have investigated the stability of mini-Lox in guanidinium hydrochloride (GdHCl) and under high pressure by fluorescence and circular dichroism spectroscopy. The denaturation experiments demonstrate that mini-Lox is a rather unstable molecule, which undergoes a two-step unfolding transition. Both chemical- and physical-induced denaturation suggest that mini-Lox is more hydrated than Lox-1, an observation also confirmed by 1-8 anilinonaphtalene sulphonic acid binding studies. We have also investigated the occurrence of substrate-induced changes in the protein tertiary structure by fluorescence techniques. In particular, eicosatetraynoic acid (ETYA), an irreversible inhibitor of lipoxygenase, has been used to mimic the effect of substrate binding. We demonstrated that mini-Lox is indeed characterized by much larger conformational changes than those occurring in the native Lox-1 upon binding of ETYA. All these findings strongly support the hypothesis that the larger hydration of mini-Lox renders this molecule more flexible and therefore less stable, that on the other hand is probably causing its higher catalytic efficiency.